2016
DOI: 10.1186/s13640-016-0140-7
|View full text |Cite
|
Sign up to set email alerts
|

Multithreading cascade of SURF for facial expression recognition

Abstract: We propose a novel and general framework called the multithreading cascade of Speeded Up Robust Features (McSURF), which is capable of processing multiple classifications simultaneously and accurately. The proposed framework adopts SURF features, but the framework is a multi-class and simultaneous cascade, i.e., a multithreading cascade. McSURF is implemented by configuring an area under the receiver operating characteristic (ROC) curve (AUC) of the weak SURF classifier for each data category into a real-value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…To learn the Oi-HOG features, we use a multithreading cascade algorithm, which appears in our previous publication [41] and the training procedure also follows the setting reported in our previous publication. The novel classification framework in the study reported in this paper is referred to as multithreading cascade of orientation-invariant histograms for oriented gradients (McOiHOG).…”
Section: B Results Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…To learn the Oi-HOG features, we use a multithreading cascade algorithm, which appears in our previous publication [41] and the training procedure also follows the setting reported in our previous publication. The novel classification framework in the study reported in this paper is referred to as multithreading cascade of orientation-invariant histograms for oriented gradients (McOiHOG).…”
Section: B Results Comparisonmentioning
confidence: 99%
“…Adopting the pre-calculated polar templates, the convergence rate for feature learning was improved by 73 minutes. To make fair comparison, we used the same learning framework and the same data (multithreading cascade [41]) for learning Oi-HOG, HOG, SURF, SIFT, and Haar features. The results are shown in Table I.…”
Section: B Results Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the proposed model must extract the parallel speech data, which can limit the process to a oneto-one conversion only. In future works, we will explore a many-to-many emotional VC method and use it in other applications, such as emotional voice recognition [25] or facial expression recognition [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, appearance-based features extraction methods encode the face appearance variations without taking muscle motion into account. Chen et al [10] introduced the multithreading cascade of Speeded Up Robust Features (McSURF), which improve the recognition accuracy rate. Cruz et al [11] explore the temporal derivative and adjacent frames by using new framework known as temporal patterns of oriented edge magnitudes.…”
Section: Related Workmentioning
confidence: 99%